Sistema hipermídia ajudando a construir a pesquisa escolar - Machado, Ana Maria Nogueira [UNESP]; Vidott, Silvana Aparecida Borsetti Gregório [UNESP] (Pontifícia Universidade Católica de Campinas, 2003)
This work was motivated by the intent to change the conditions in which elementary school students, from 1rst to 4rth grade use to come to the library in order to do school-research. This article's objective is to discuss the development of the Hypermedia System Helping to build the elementary-school research, focusing on reference elaboration, in accordance with the NBR 6023/2000 of the Brazilian Association of Technical Norms. The system was built in the software Personal Brain TM that has structural characteristics in net form. The latter make possible to create an informational hypermedia environment, personal or shared, in a natural relationship between the document-stored information and the themes approached by the users. The discussed hypermedia system seems apt to become a motivating tool for the school research.

Este trabalho surgiu da constatação das condições em que alunos de 1ª a 4ª séries do 1º grau, hoje ensino fundamental, vinham à biblioteca para elaborar a chamada pesquisa escolar. O objetivo deste artigo é discutir o desenvolvimento do sistema hipermídia Ajudando a construir a pesquisa escolar, com enfoque na elaboração de referências, de acordo com a NBR 6023/2000 da Associação Brasileira de Normas Técnicas. O sistema foi construído no software Personal BrainTMque possui características estruturais em forma de rede. Estas possibilitam a criação de um ambiente hipermídia informacional, pessoal ou coletivo, numa relação natural entre as informações armazenadas em documentos e os temas abordados pelos usuários. Acredita-se que o sistema aqui discutido, pode ser utilizado como um instrumento motivador da pesquisa escolar.
The Hypermedia System Helping to build the elementary-school research
Keywords: pesquisa escolar; sistema hipermídia educacional; NBR 6023 - Referências; motivação; Personal Brain TM; school research; educational hypermedia system N B R 6023 _ references; Personal Brain TM